P76 | PERICAPILLARY SPACES IN THE SHEEP PINEAL GLAND – 2D AND 3D ANALYSIS (European Journal of Histochemistry)
The structural organization of pericapillary spaces in the mammalian pineal gland varies significantly among species. In rats - the most widely used in pineal research - fenestrated capillaries are surrounded by wide pericapillary spaces rich in pinealocyte processes. Notably, the rat pineal gland is among the few brain structures that lack a blood-brain barrier. In contrast, species such as squirrels, rabbits and pigs exhibit non-fenestrated capillaries with relatively narrow pericapillary spaces. The sheep pineal gland is considered a more suitable model for human studies than the rat pineal gland. This study aimed to provide a detailed ultrastructural analysis of the pericapillary spaces in the pineal gland of 9-monthold sheep using both 2D and 3D electron microscopy. Ultrathin sections were mounted on silicon wafers and imaged with a SenseBSD detector in a Gemini 450 SEM (Zeiss). Additionally, serial block-face imaging (SBFI) was performed using the 3View 2XP system (Gatan) in the same microscope. The analysis revealed that the capillaries consisted of a continuous layer of non-fenestrated endothelial cells resting on the basement membrane. Numerous pericytes were present and enclosed by their own basal membranes. The capillaries were surrounded by a thick layer of collagen fibers, itself completely enclosed by the basement membrane. The outer surface of this membrane was lined with flattened astrocytic processes (“leaflets”) that adhered tightly to each other, forming a barrier that fully separated the pericapillary space from the pineal parenchyma. SBFI showed that these astrocytic leaflets originated as terminal expansions or flattened segments along astrocytic processes. The astrocytic processes forming leaflets were extremely long and often extended beyond the imaged volume (72×72×50 µm), with no visible connections to their cell bodies. Notably, no direct contact was observed between pinealocyte processes and the basement membrane surrounding the collagen layer. Our findings indicate that the sheep pineal gland possesses a unique blood - pineal barrier. Supported by the Ministry of Science under the “Regional Initiative of Excellence” program.